2006
DOI: 10.1103/physrevb.73.155422
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laser cooling of rare-earth-ion-doped nanocrystalline powders

Abstract: The enhanced laser cooling performance of rare-earth-ion-doped nanocrystalline powders is predicted, compared to the bulk material, using Yb 3+ :Y 2 O 3 as the model material. This is achieved by enhancing the off-resonance, phonon-assisted absorption, which is proportional to the three factors considered in this paper: the dopant concentration, the pumping field energy, and the excitation coefficient. Using the energy transfer theory for concentration quenching, the optimum concentration corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 48 publications
2
40
0
1
Order By: Relevance
“…Note that the thin film h-BN shows low and high-energy enhancement and scatter in D p due to the substrate phonon. 15,16 Xenon and Fluorine have eight and seven valence electrons, respectively, so XeF 6 consists of six Xe-F bonds and one lone electron pair as shown in Fig. 2(a).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the thin film h-BN shows low and high-energy enhancement and scatter in D p due to the substrate phonon. 15,16 Xenon and Fluorine have eight and seven valence electrons, respectively, so XeF 6 consists of six Xe-F bonds and one lone electron pair as shown in Fig. 2(a).…”
Section: Introductionmentioning
confidence: 99%
“…Other nonequilibrium phonon harvesting schemes have received attention for their ability to surpass the TE limits in scale and efficiency. These include the laser cooling of ion-doped materials through antiStokes florescence 11,12 , and the use of in-situ electron barriers to recycle phonons emitted during the Joule heating 13,14 . Conversely, the pV cell focuses on power generation.…”
Section: Introductionmentioning
confidence: 99%
“…Ruan and Kaviany have theoretically demonstrated that the cooling efficiency can be dramatically enhanced then host material containes rare-ion-doped nanocrystalline powder (Ruan & Kaviany, 2006). Light localization effects increase the photon density, leading to an enhanced absorptivity and the phonon spectrum is modified due to finite size of the nanopowder.…”
Section: Laser Cooling Of Rare-earth Doped Solidsmentioning
confidence: 99%